Higher site productivity and stand age enhance forest susceptibility to drought-induced mortality - Socha, Jarosław; Hawryło, Paweł; Tymińska-Czabańska, Luiza; Reineking, Björn; Lindner, Marcus; Netzel, Paweł; Grabska-Szwagrzyk, Ewa; Vallejos, Ronny; Reyer, Christopher P.O. (Agricultural and forest meteorology, 2023)
•Scots pine mortality is driven by climatic water balance.•The probability of drought-induced mortality is affected by stand age and site index.•The oldest stands show the highest susceptibility to drought-induced mortality.•Enhanced mortality probability is observed in most productive sites. Warmer and drier conditions increase forest mortality worldwide. At the same time, nitrogen deposition, longer growing seasons and higher atmospheric CO2 concentrations may increase site productivity accelerating forest growth. However, tree physiological studies suggest that increased site productivity can also have adverse effects, reducing adaptation to drought. Understanding such intricate interactions that might foster tree mortality is essential for designing activities and policies aimed at preserving forests and the ecosystem services they provide. This study shows how site factors and stand features affect the susceptibility of Scots pine to drought-induced stand-level mortality. We use extensive forest data covering 750,000 ha, including 47,450 managed Scots pine stands, of which 2,547 were affected by mortality during the drought in 2015–2019. We found that the oldest and most dense stands growing on the most productive sites showed the highest susceptibility to enhanced mortality during drought. Our findings suggest that increasing site productivity may accelerate the intensity and prevalence of drought-induced forest mortality. Therefore, climate change may increase mortality, particularly in old and high-productive forests. Such exacerbated susceptibility to mortality should be considered in forest carbon sink projections, forest management, and policies designed to increase resilience and protect forest ecosystems.